PENGARUH MOTIVASI BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA PESERTA DIDIK KELAS III SDN SETIA ASIH 01 - Zamie, Fariha Fathiyya; Mujazi, Mujazi (IPI Press, 2024)
This study aims to identify whether there is an influence of learning motivation on critical thinking skills in mathematics. The study employs a quantitative approach using a survey method. The population includes all third-grade students at SDN Setia Asih 01, with a sample of 25 students selected through purposive sampling. The results show that based on the partial t-test, the significance value α 0.00 is less than 0.05, with a t-value of 4.107, which is greater than the t-table value of 2.069. Therefore, H0 is rejected, and H1 is accepted, indicating that learning motivation affects critical thinking skills in mathematics. The coefficient of determination shows an R Square value of 0.423, meaning that learning motivation influences 42.3% of the critical thinking skills in mathematics. In conclusion, learning motivation impacts the critical thinking skills in mathematics of third-grade students at SDN Setia Asih 01.